Relationship of the knee extensor strength but not the quadriceps femoris muscularity with sprint performance in sprinters: a reexamination and extension - Miyuki Hori; Tadashi Suga; Masafumi Terada; Takahiro Tanaka; Yuki Kusagawa; Mitsuo Otsuka; Akinori Nagano; Tadao Isaka (BMC, 2021)
Abstract Purpose This study examined the relationships of knee extensor strength and quadriceps femoris size with sprint performance in sprinters. Methods Fifty-eight male sprinters and 40 body size-matched male non-sprinters participated in this study. The knee extensor isometric and isokinetic strengths were measured using a dynamometer. The isokinetic strength measurements were performed with slow and fast velocities at 60°/s and 180°/s, respectively. The quadriceps femoris muscle volume (MV) was measured using magnetic resonance imaging. The relative knee extensor strengths and quadriceps femoris MV were calculated by normalizing to body mass. Results Absolute and relative knee extensor strengths during two velocity isokinetic contractions, but not during isometric contraction, were significantly higher in sprinters than in non-sprinters (P = 0.047 to < 0.001 for all). Such a significant difference was also observed for relative quadriceps femoris MV (P = 0.018). In sprinters, there were positive correlations between all three knee extensor strengths and quadriceps femoris MV (r = 0.421 to 0.531, P = 0.001 to < 0.001 for all). The absolute and relative strengths of the fast-velocity isokinetic knee extension correlated negatively with personal best 100-m sprint time (r = −0.477 and −0.409, P = 0.001 and < 0.001, respectively). In contrast, no such significant correlations were observed between absolute and relative quadriceps femoris MVs and personal best 100-m sprint time. Conclusions These findings suggest that despite the presence of the relationship between muscle strength and size, the knee extensor strength may be related to superior sprint performance in sprinters independently of the quadriceps femoris muscularity.